The contributions of islam and muslim scholars to infection control: Dealing with contagious diseases and pandemics - Ahmed S BaHammam (Wolters Kluwer Medknow Publications, 2022)
Islam's teachings emphasize maintaining personal hygiene and isolating sick people, both of which are crucial in the present COVID-19 pandemic. Between the 7th and 15th centuries, Islamic and Arab civilizations produced significant advancements in science and medicine. These discoveries laid the groundwork for the development of the European Renaissance. In Islam, maintaining one's personal cleanliness and hygiene is a duty that Muslims have to do to worship Allah (God). In universal outbreaks such as plague pandemics, Islam recognized the risks and mandated precautions, prevention, and hygienic isolation. Islam took the lead in pioneering several health protection practices, such as the quarantine rule. If a contagious sickness manifests in a certain area or town, Prophet Muhammad instructed to forbid entry or exit to the affected town, now known as quarantine. The first documented application of quarantine, as we currently know, it was implemented by the Muslim scholar Avicenna (ibn Sina). According to Islam, protecting living creatures' lives equals protecting the faith. Therefore, all needed measures to reduce the risk of infection, including vaccines, should be rigorously applied in Islam. In this viewpoint, we discuss Islamic beliefs, the Prophet's practices and teachings, and Muslim scholars' contributions to lowering infections and putting specific regulations in place during pandemics that supplemented the development of infection control rules as we know them in modern medical practices through using the best available evidence.